Corporate characteristics and voluntary disclosure of Malaysian listed corporation / Norashikin Ismail - Ismail, Norashikin (Universiti Teknologi MARA Cawangan Pahang, 2002)
The term" voluntary disclosure" has been variously defined to include reporting on profit forecast and projection, corporate achievement, corporate mission and value added statement. There are currently neither legal requirements nor accounting pronouncements to regulate disclosures in these aspects. In Malaysia quantified profit forecast disclosure is only required when a company issues a prospectus in an initial public offering. The purpose of the study was to investigate the level of Malaysian corporate voluntary disclosure and its association with size, profitability, institutional holdings and auditor's reputation. Data collected were analyzed using SPSS. The general findings showed that then level of company disclosure is lower than the external users considered desirable. Correlation study using Pearson Correlation indicated a statistical significant positive relationship between disclosures level and total assets, total equity, share capital and net profit for plantation and industrial products companies, while trading and services companies showed only a positive correlation between disclosure and sales turnover. Auditor's reputation shows no effect on voluntary disclosure for all three industries under review. Companies were willing to disclose only information that is not considered sensitive.